Joint and elastic wave element
By using a silicon oxide bonding layer with a low oxygen ratio between the piezoelectric material substrate and the support substrate containing metal oxides and an amorphous layer with a high oxygen ratio, the problem of insolid bonding is solved, and stable bonding and Improve insulation effect.
Patent Information
- Application Number
- CN201980067455.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-10-17
- Filing Date
- 2019-08-23
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2039-08-23
AI Technical Summary
The prior art is difficult to firmly and stably bond the piezoelectric material substrate to a support substrate containing metal oxides, and peeling is prone to occur during processing.
By using the composition of Si(1-x)Ox in the bonding layer, a silicon oxide bonding layer with a low oxygen ratio is formed, and an amorphous layer with a high oxygen ratio is provided between the bonding layer and the support substrate to improve bonding strength.
The firm and stable bonding of the piezoelectric material substrate and the support substrate containing metal oxide is achieved, thereby avoiding the problem of peeling during processing, and improving the insulating property of the joint.
Smart Images

Figure CN112868178B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a piezoelectric material substrate and a bonding assembly with a support substrate comprising a metal oxide. Background Technology
[0002] Known examples include: elastic surface wave devices used in mobile phones that function as filters and oscillators; Lamb wave elements using piezoelectric thin films; and thin-film resonators (FBARs). Among these elastic wave devices, there are those in which a support substrate is bonded to a piezoelectric substrate that propagates elastic surface waves, and comb-shaped electrodes capable of exciting elastic surface waves are disposed on the surface of the piezoelectric substrate. By bonding a support substrate with a coefficient of thermal expansion smaller than that of the piezoelectric substrate to the piezoelectric substrate in this way, changes in the size of the piezoelectric substrate due to temperature variations are suppressed, thereby suppressing changes in the frequency characteristics of the elastic surface wave device.
[0003] It is known that when bonding a piezoelectric substrate to a silicon substrate, a silicon oxide film is formed on the surface of the piezoelectric substrate, and the piezoelectric substrate and the silicon substrate are directly bonded through the silicon oxide film (Patent Document 1). In this bonding process, a plasma beam is irradiated onto the surface of the silicon oxide film and the surface of the silicon substrate to activate the surfaces and perform direct bonding (plasma activation method).
[0004] In addition, it is known that the surface of a piezoelectric substrate is roughened, a filler layer is provided on the roughened surface to planarize it, and the filler layer is bonded to a silicon substrate via an adhesive layer (Patent Document 2). In this method, epoxy-based and acrylic-based resins are used in the filler layer and the adhesive layer. By roughening the bonding surface of the piezoelectric substrate, the reflection of bulk waves is suppressed and parasitic signals are reduced.
[0005] In addition, a direct bonding method using the so-called FAB (Fast Atom Beam) method is known (Patent Document 3). In this method, each bonding surface is activated by irradiating a neutralized atomic beam at room temperature to perform direct bonding.
[0006] On the other hand, Patent Document 4 describes a method where a piezoelectric material substrate is directly bonded to a support substrate containing ceramics (alumina, aluminum nitride, silicon nitride) via an intermediate layer, instead of being directly bonded to a silicon substrate. The intermediate layer is made of silicon, silicon oxide, silicon nitride, or aluminum nitride.
[0007] Existing technical documents
[0008] Patent documents
[0009] Patent Document 1: U.S. Patent No. 7,213,314,B2
[0010] Patent Document 2: Japanese Patent No. 5814727
[0011] Patent Document 3: Japanese Patent Application Publication No. 2014-086400
[0012] Patent Document 4: Japanese Patent No. 3774782
[0013] Patent Document 5: PCT / JP2018 / 011256 Summary of the Invention
[0014] Depending on the intended use of the bonding layer, it is desirable to improve insulation by increasing the resistance in the bonding layer. For example, in the case of elastic wave elements, improving the insulation of the bonding layer can reduce noise and losses. Therefore, the applicant of this application disclosed that a bonding layer with high insulation is formed by making the composition of the bonding layer a silicon oxide with a low oxygen ratio (Patent Document 5).
[0015] However, it is sometimes difficult to firmly and stably bond the piezoelectric material substrate to the support substrate containing metal oxide via a bonding layer containing silicon oxide with a low oxygen ratio. Peeling may sometimes occur when the piezoelectric material substrate is subjected to processing such as grinding.
[0016] The objective of this invention is to firmly and stably bond a piezoelectric material substrate to a support substrate containing a metal oxide via a bonding layer comprising a silicon oxide with a low oxygen ratio.
[0017] The present invention is characterized by having:
[0018] A support substrate comprising a metal oxide;
[0019] piezoelectric material substrate;
[0020] A bonding layer is disposed between the supporting substrate and the piezoelectric material substrate, and is composed of Si. (1-x) O x (0.008≤x≤0.408); and
[0021] An amorphous layer is disposed between the bonding layer and the supporting substrate.
[0022] The oxygen ratio in the amorphous layer is higher than the oxygen ratio in the supporting substrate.
[0023] In addition, the present invention relates to an elastic wave element, characterized in that,
[0024] It includes: the bonding body and an electrode disposed on the piezoelectric material substrate.
[0025] Invention Effects
[0026] According to the present invention, a piezoelectric material substrate can be firmly and stably bonded to a support substrate containing metal oxide via a bonding layer comprising a silicon oxide with a low oxygen ratio. Attached Figure Description
[0027] Figure 1 In the diagram, (a) indicates a state in which a bonding layer 2 is provided on a piezoelectric material substrate 4, (b) indicates a state in which the surface 2b of the bonding layer 2A is activated by a neutral beam A, and (c) indicates a state in which the surface 1a of the support substrate 1 is activated by a neutral beam A.
[0028] Figure 2 In the diagram, (a) indicates the state in which the piezoelectric material substrate 4 and the support substrate 1 are joined together, (b) indicates the state in which the piezoelectric material substrate 4A is thinned through processing, and (c) indicates the state in which an electrode 6 is provided on the piezoelectric material substrate 4A.
[0029] Figure 3 In the diagram, (a) indicates a state in which an intermediate layer 11 and a bonding layer 2 are provided on a piezoelectric material substrate 4, (b) indicates a state in which the surface 2b of the bonding layer 2A is activated by a neutral beam A, and (c) indicates a state in which the surface 1a of the support substrate 1 is activated by a neutral beam A.
[0030] Figure 4 In the diagram, (a) indicates the state in which the piezoelectric material substrate 4 and the support substrate 1 are joined together, (b) indicates the state in which the piezoelectric material substrate 4A is thinned through processing, and (c) indicates the state in which an electrode 6 is provided on the piezoelectric material substrate 4A. Detailed Implementation
[0031] The present invention will now be described in detail with appropriate reference to the accompanying drawings.
[0032] Figure 1 , Figure 2 This is a schematic diagram illustrating a manufacturing example of directly bonding a support substrate to a piezoelectric material substrate.
[0033] like Figure 1 As shown in (a), a bonding layer 2 is formed on the main surface 4a of the piezoelectric material substrate 4. 4b is the main surface on the opposite side of the piezoelectric material substrate 4. Next, as... Figure 1 As shown in (b), a neutral beam is irradiated onto the surface 2a of the bonding layer 2 as indicated by arrow A, thereby activating the surface of the bonding layer 2 and creating an activated surface 2b. On the other hand, as... Figure 1 As shown in (c), a neutral beam A is irradiated onto the main surface 1a of the support substrate 1 to activate it, thereby obtaining a support substrate 1 with an activated surface. 1b is the main surface opposite to the activated surface.
[0034] Next, as Figure 2As shown in (a), the activated surface of the bonding layer and the activated surface 1a of the support substrate 1 are directly bonded together to obtain the bond body 5. Here, by controlling the output of the neutral beam A or the irradiation time, an amorphous layer 10 can be generated along the bonding interface between the activated surface 1a of the support substrate 1 and the bonding layer 2B.
[0035] In a preferred embodiment, the surface 4b of the piezoelectric material substrate 4 of the bonding body 5 is further ground, such as... Figure 2 As shown in (b), the thickness of the piezoelectric material substrate 4A is reduced to obtain the bonding body 5A. 4c is a polished surface.
[0036] Figure 2 In (c), a specified electrode 6 is formed on the polished surface 4c of the piezoelectric material substrate 4A, thereby fabricating an elastic wave element 7.
[0037] Figure 3 , Figure 4 In one embodiment, an intermediate layer 11 is provided between the piezoelectric material substrate 4 and the bonding layers 2, 2A, and 2B.
[0038] That is, such as Figure 3 As shown in (a), an intermediate layer 11 and a bonding layer 2 are sequentially formed on the main surface 4a of the piezoelectric material substrate 4. Next, as... Figure 3 As shown in (b), a neutral beam is irradiated onto the surface 2a of the bonding layer 2 as indicated by arrow A, thereby activating the surface of the bonding layer 2A and creating the activated surface 2b. On the other hand, as... Figure 3 As shown in (c), a neutral beam A is irradiated onto the main surface 1a of the support substrate 1 to activate it, thereby obtaining a support substrate 1 with an activated surface. 1b is the main surface opposite to the activated surface.
[0039] Next, as Figure 4 As shown in (a), the activated surface of the bonding layer and the activated surface 1a of the support substrate 1 are directly bonded together to obtain the bond body 15. Here, by controlling the output of the neutral beam A or the irradiation time, an amorphous layer 10 can be generated along the bonding interface between the activated surface 1a of the support substrate 1 and the bonding layer 2B.
[0040] In a preferred embodiment, the surface 4b of the piezoelectric material substrate 4 of the bonding body 15A is further ground, such as... Figure 4 As shown in (b), the thickness of the piezoelectric material substrate 4A is reduced to obtain the bonding body 15A. 4c is a polished surface.
[0041] Figure 4 In (c), a specified electrode 6 is formed on the polished surface 4c of the piezoelectric material substrate 4A, thereby fabricating an elastic wave element 17.
[0042] In this invention, the supporting substrate comprises a metal oxide. This metal oxide can be an oxide of a single metal or a composite oxide of multiple metals. Preferably, the metal oxide is selected from the group consisting of free silicon aluminum oxynitride ceramics, sapphire, cordierite, andalusite, and alumina. The alumina is preferably transparent alumina.
[0043] From the viewpoint of bonding strength, the relative density of the support substrate is preferably 95.5% or higher, and can be 100%. The relative density is determined using the Archimedes method. Furthermore, the method of manufacturing the support substrate is not particularly limited, but a sintered body is preferred.
[0044] Silicon-aluminum-oxygen-nitrogen ceramics are ceramics obtained by sintering a mixture of silicon nitride and aluminum oxide, and have the following composition.
[0045] Si 6-z Al z O z N 8-z
[0046] That is, the silicon-aluminum-oxygen-nitrogen ceramic has a composition in which alumina is mixed in silicon nitride, and z represents the mixing ratio of alumina. z is more preferably 0.5 or more. In addition, z is more preferably 4.0 or less.
[0047] Sapphire is a single crystal with an Al₂O₃ composition, while alumina is a polycrystalline material with an Al₂O₃ composition. Cordierite is a ceramic with a composition of 2MgO·2Al₂O₃·5SiO₂. Andalusite is a ceramic with a composition ranging from 3Al₂O₃·2SiO₂ to 2Al₂O₃·SiO₂.
[0048] The substrate material for the piezoelectric material is not limited as long as it possesses the desired piezoelectricity, but a single crystal with the composition LiAO3 is preferred. Here, A is one or more elements selected from the group consisting of niobium and tantalum. Therefore, LiAO3 can be lithium niobate, lithium tantalate, or a lithium niobate-lithium tantalate solid solution.
[0049] In this invention, a bonding layer is provided between a support substrate and a piezoelectric material substrate, the bonding layer being composed of Si. (1-x) O x (0.008≤x≤0.408).
[0050] This composition is characterized by a significantly lower oxygen ratio compared to SiO2 (corresponding to x = 0.667). If silicon oxides containing this composition are used... (1-x) O x By bonding the piezoelectric material substrate to the support substrate through the bonding layer, the insulation in the bonding layer can be improved.
[0051] In the Si constituting the bonding layer(1-x) O x In the composition, if x is less than 0.008, the resistance in the bonding layer decreases, and the desired insulation cannot be obtained. Therefore, x is set to 0.008 or more, preferably 0.010 or more, more preferably 0.020 or more, and particularly preferably 0.024 or more. Furthermore, if x is greater than 0.408, the bonding strength decreases, and peeling of the piezoelectric material substrate easily occurs. Therefore, x is set to 0.408 or less, more preferably 0.225 or less.
[0052] The resistivity of the bonding layer is preferably 4.8 × 10⁻⁶. 3 Ω·cm or higher, more preferably 5.8×10 3 Ω·cm or higher, with a particularly preferred value of 6.2 × 10⁻⁶. 3 Ω·cm or higher. On the other hand, the resistivity of the bonding layer is typically 1.0 × 10⁻⁶. 8 Below Ω·cm.
[0053] The thickness of the bonding layer is not particularly limited, but from the point of view of manufacturing cost, it is preferably 0.01 to 10 μm, and more preferably 0.01 to 0.5 μm.
[0054] The method for forming the bonding layer is not limited, but examples include sputtering, chemical vapor deposition (CVD), and evaporation. Here, it is particularly preferred that, in reactive sputtering with Si as the sputtering target, the oxygen ratio (x) of the bonding layer can be controlled by adjusting the amount of oxygen flowing into the chamber.
[0055] The specific manufacturing conditions for the bonding layer depend on the chamber specifications and are therefore selected appropriately. In a preferred embodiment, the total pressure is set to 0.28–0.34 Pa and the oxygen partial pressure to 1.2 × 10⁻⁶ Pa. ―3 ~5.7×10 -2 Pa is used to maintain the film formation temperature at room temperature. Additionally, boron-doped Si can be used as a Si target. As described later, the amount of boron (B) as an impurity at the interface between the bonding layer and the support substrate 1 is controlled to be 5 × 10⁻⁶. 18 atoms / cm 3 ~5×10 19 atoms / cm 3 Left and right. This allows for more reliable assurance of insulation in the bonding layer.
[0056] In a preferred embodiment, the active surface of the bonding layer and the active surface of the support substrate are directly bonded. In other words, a bonding interface is formed along the interface between the bonding layer and the support substrate. In this case, the arithmetic mean roughness Ra of the active surface of the bonding layer is preferably 1 nm or less, more preferably 0.3 nm or less. Furthermore, the arithmetic mean roughness Ra of the active surface of the support substrate is preferably 1 nm or less, more preferably 0.3 nm or less. This further improves the bonding strength between the support substrate and the bonding layer.
[0057] The bonding assembly of the present invention further comprises an amorphous layer formed between the bonding layer and the support substrate, wherein the oxygen ratio in the amorphous layer is higher than the oxygen ratio in the support substrate. That is, although the amorphous layer is formed along the activation surface of the support substrate, it has been found that oxygen diffusion occurs in this amorphous layer, and sometimes the oxygen ratio in the amorphous layer is higher than the oxygen ratio of the metal oxide constituting the support substrate. Furthermore, it has been found that when oxygen diffusion occurs in this manner, the bonding strength of the piezoelectric material substrate on the support substrate is improved; for example, even when the piezoelectric material substrate is thinned through processing, peeling of the piezoelectric material substrate is less likely to occur.
[0058] In a preferred embodiment, the amorphous layer is primarily composed of the metal, oxygen (O), and argon (Ar) that constitute the support substrate. Specifically, when the support substrate comprises silicon-aluminum-oxygen-nitrogen ceramic, the amorphous layer is primarily composed of silicon (Si), aluminum (Al), nitrogen (N), oxygen (O), and argon (Ar) that constitute the support substrate. "Primary component" means that, when the total atomic percentage is 100 atomic%, the total atomic percentage of the aforementioned atoms is 95 atomic% or more, more preferably 97 atomic% or more. Particularly preferred is that the composition of the amorphous layer is the same as the composition of the support substrate material, but the oxygen percentage is higher than that of the support substrate material, and it contains argon.
[0059] In this invention, the oxygen ratio in the amorphous layer is higher than the oxygen ratio in the supporting substrate. From the viewpoint of improving bonding strength, this difference in oxygen ratio is preferably 0.5 atomic% or more, more preferably 1.0 atomic% or more. Furthermore, practically, this difference in oxygen ratio is preferably 7.0 atomic% or less.
[0060] Furthermore, from the viewpoint of improving bonding strength, the atomic ratio of argon (Ar) in the amorphous layer is preferably 1.0 atomic% or more, more preferably 1.5 atomic% or more. Additionally, the atomic ratio of argon (Ar) in the amorphous layer is preferably 5.0 atomic% or less, more preferably 4.8 atomic% or less.
[0061] The material of the intermediate layer can be any material that bonds with the bonding layer and the piezoelectric material substrate, and there is no particular limitation. Preferred materials are SiO2, Ta2O5, TiO2, ZrO2, HfO2, Nb2O3, Bi2O3, Al2O3, MgO, AlN, and Si3N4.
[0062] In particular, when dealing with high frequencies (such as the 3.5–6 GHz band for 5G communication), it is necessary to increase the frequency of elastic waves. In this case, the material of the intermediate layer is preferably a hypersonic material. The speed of sound of this hypersonic material is preferably 6000 m / s or more, more preferably 10000 m / s or more. There is no particular upper limit to the speed of sound of the intermediate layer material, but in practice it is difficult to exceed 30000 m / s. Therefore, its upper limit is 30000 m / s or less, and in most cases, it is 25000 m / s or less. Examples of such hypersonic materials include AlN and Si3N4. Furthermore, the speed of sound of the material is calculated based on the density (JIS C2141), Young's modulus (JIS R1602), and Poisson's ratio (JIS R1602) obtained using the JIS method.
[0063] Furthermore, when dealing with high frequencies (such as the 3.5–6 GHz band for 5G communication), high-power signals are input, necessitating improved heat dissipation. In this case, it is preferable to use a material with high thermal conductivity for the intermediate layer. The thermal conductivity of this material is preferably 100 W / (m·K) or higher, more preferably 900 W / (m·K) or higher, and particularly preferably 1000 W / (m·K). There is no particular upper limit to the thermal conductivity of the intermediate layer material; however, it is practically difficult to exceed 5000 W / (m·K), therefore, its upper limit is 5000 W / (m·K) or lower, and most are 3000 W / (m·K) or lower. Examples of such high thermal conductivity materials include AlN and Si3N4. The thermal conductivity of the material is measured according to JIS R1611.
[0064] The constituent elements of the present invention will be further described below.
[0065] The application of the connector of the present invention is not particularly limited; for example, it can be preferably applied to elastic wave elements and optical elements.
[0066] As elastic wave elements, known examples include surface wave devices, Lamb wave elements, and thin-film resonators (FBARs). For instance, an elastic surface wave device has an IDT (Interdigital Transducer) electrode (also called a comb electrode or curtain electrode) on the input side of a piezoelectric material substrate to excite the elastic surface wave, and an IDT electrode on the output side to receive the elastic surface wave. If a high-frequency signal is applied to the IDT electrode on the input side, an electric field is generated between the electrodes, exciting the elastic surface wave, which then propagates on the piezoelectric material substrate. Furthermore, the propagating elastic surface wave can be output as an electrical signal from the IDT electrode on the output side, which is positioned in the propagation direction.
[0067] A metal film can be present on the bottom surface of the piezoelectric material substrate. When manufacturing a Lamb wave element as an elastic wave device, the metal film increases the electromechanical coupling coefficient near the back surface of the piezoelectric material substrate. In this case, the Lamb wave element has the following structure: a comb-tooth electrode is formed on the surface of the piezoelectric material substrate, and the metal film of the piezoelectric material substrate is exposed by a cavity provided in the support substrate. Examples of materials for such a metal film include aluminum, aluminum alloys, copper, and gold. It should be noted that, in manufacturing a Lamb wave element, a composite substrate having a piezoelectric material layer without a metal film on the bottom surface can be used.
[0068] Furthermore, a metal film and an insulating film can be formed on the bottom surface of the piezoelectric material substrate. When manufacturing a thin-film resonator as an elastic wave device, the metal film functions as an electrode. In this case, the thin-film resonator has the following structure: electrodes are formed on the surface and back of the piezoelectric material substrate, and the metal film of the piezoelectric material substrate is exposed by making the insulating film a cavity. Examples of materials for such metal films include molybdenum, ruthenium, tungsten, chromium, and aluminum. Examples of materials for the insulating film include silicon dioxide, phosphosilicate glass, and borosilicate glass.
[0069] Furthermore, examples of optical elements include optical switching elements, wavelength conversion elements, and optical modulation elements. Additionally, periodic polarization reversal structures can be formed in piezoelectric material substrates.
[0070] The present invention pertains to elastic wave elements. When the piezoelectric material substrate is made of lithium tantalate, a piezoelectric material substrate with a direction centered on the X-axis (the direction of elastic surface wave propagation) and rotated 36–47° (e.g., 42°) from the Y-axis to the Z-axis is preferred due to its low propagation loss. Furthermore, when the piezoelectric material substrate comprises lithium niobate, a piezoelectric material substrate with a direction centered on the X-axis (the direction of elastic surface wave propagation) and rotated 60–68° (e.g., 64°) from the Y-axis to the Z-axis is preferred due to its low propagation loss. Moreover, the size of the piezoelectric material substrate is not particularly limited; for example, a diameter of 50–150 mm and a thickness of 0.2–60 μm are acceptable.
[0071] To obtain the assembly of the present invention, the following method is preferred.
[0072] First, the surfaces of the bonding layer and the support substrate (bonding surfaces) are planarized to obtain a flat surface. Methods for planarizing these surfaces include lapping and chemical mechanical polishing (CMP). Furthermore, it is preferable that the flat surface has a Ra ≤ 1 nm, and more preferably 0.3 nm or less.
[0073] Next, the surfaces of the bonding layer and the support substrate are cleaned to remove abrasive residue and processing-degraded layers. Surface cleaning methods include wet cleaning, dry cleaning, and brushing; brushing is preferred for a simple and efficient way to obtain a clean surface. In this case, it is particularly preferred to use Sunwash LH540 as the cleaning solution, and then use a brushing machine to clean the surface using a mixture of acetone and IPA.
[0074] Next, each flat surface is activated by irradiating the surface of the bonding layer and the surface of the supporting substrate with a neutral beam.
[0075] When performing surface activation using a neutral beam, it is preferable to use the apparatus described in Patent Document 3 to generate the neutral beam for irradiation. Specifically, a saddle-type high-speed atomic beam source is used as the beam source. Then, an inert gas is introduced into the chamber, and a high voltage is applied to the electrodes from a DC power supply. Thereby, utilizing the saddle-type electric field generated between the electrodes (positive electrode) and the casing (negative electrode), electrons (e) move and generate a beam of atoms and ions produced by the inert gas. In the beam reaching the grid, the ion beam is neutralized at the grid, thus a beam of neutral atoms is emitted from the high-speed atomic beam source. The atomic species constituting the beam are preferably inert gases (argon, nitrogen, etc.).
[0076] When activating by beam irradiation, the preferred voltage is 0.5–2.0 kV, and the preferred current is 50–200 mA.
[0077] Next, the activated surfaces are brought into contact and joined in a vacuum atmosphere. The temperature at this time is room temperature, specifically, preferably 40°C or lower, more preferably 30°C or lower. Furthermore, the joining temperature is particularly preferably 20°C or higher and 25°C or lower. The joining pressure is preferably 100 to 20000 N.
[0078] Example
[0079] (Examples 1, 2, 3; Comparative Examples 1, 2)
[0080] According to reference Figure 1 and Figure 2 The method described herein is used to prepare the joints 5 and 5A for the examples shown in Tables 1 and 2.
[0081] Specifically, a lithium tantalate substrate (LT substrate) with an OF section, a diameter of 4 inches, and a thickness of 250 μm was used as the piezoelectric material substrate 4. The LT substrate was cut at 46°Y with the surface wave (SAW) propagation direction as X and the cutting angle as rotation Y. The surface 4a of the piezoelectric material substrate 4 was mirror-polished to achieve an arithmetic mean roughness Ra of 0.3 nm. Ra was measured using an atomic force microscope (AFM) with a field of view of 10 μm × 10 μm.
[0082] Next, a bonding layer 2 is formed on the surface 4a of the piezoelectric material substrate 4 using DC sputtering. Boron-doped Si is used as the target. Oxygen is introduced as an oxygen source. The total pressure and partial pressure of the atmosphere within the chamber are changed by varying the amount of oxygen introduced, thereby altering the oxygen ratio of the bonding layer 2. The thickness of the bonding layer 2 is set to 100–200 nm. The arithmetic mean roughness Ra of the surface 2a of the bonding layer 2 is 0.2–0.6 nm. Next, the bonding layer 2 is subjected to chemical mechanical polishing (CMP) to achieve a film thickness of 80–190 nm and an Ra value of 0.08–0.4 nm.
[0083] On the other hand, as the support substrate 1, a support substrate 1 containing silicon aluminum oxynitride ceramic (z = 2.5) with an orientation plane (OF) portion, a diameter of 4 inches, and a thickness of 500 μm was prepared. The surfaces 1a and 1b of the support substrate 1 were finished by chemical mechanical polishing (CMP) to achieve an arithmetic mean roughness Ra of 0.2 nm.
[0084] Next, the flat surface 2b of the bonding layer 2A and the surface 1a of the support substrate 1 are cleaned to remove dirt, and then introduced into the vacuum chamber. A vacuum is then drawn until 10... -6After passing through multiple pressures, the bonding surfaces 1a and 2b of each substrate were irradiated with a high-speed atomic beam for 120 seconds (accelerating voltage 1 kV, Ar flow rate 27 sccm). Next, the irradiated surface (activation surface) 2b of the bonding layer 2A was brought into contact with the activation surface 1a of the supporting substrate 1, and bonding was performed by applying a pressure of 10000 N for 2 minutes (see reference). Figure 2 (a)). Next, the resulting joints 5 were heated at 100°C for 20 hours.
[0085] Next, the surface 4b of the piezoelectric material substrate 4 is ground and polished to reduce the thickness from the initial 250 μm to 1 μm (refer to...). Figure 2 (b)).
[0086] For the obtained joints 5 and 5A, the following characteristics are evaluated.
[0087] (Confirmation of the amorphous layer)
[0088] The presence of the amorphous layer is observed below.
[0089] Measuring apparatus:
[0090] Microstructures were observed using a transmission electron microscope (Hitachi High Technology H-9500).
[0091] Measurement conditions:
[0092] For samples thinned using the FIB (Focused Ion Beam) method, observations were conducted at an accelerating voltage of 200 kV.
[0093] (The ratio of oxygen atoms to argon atoms in the bonding layer, supporting substrate, and amorphous layer)
[0094] The following apparatus was used to perform elemental analysis using an EDS (energy dispersive X-ray spectrometer) to determine the ratio of oxygen atoms to argon atoms in the bonding layer, the supporting substrate, and the amorphous layer.
[0095] Measuring apparatus:
[0096] Elemental analysis was performed using an elemental analysis apparatus (JEOL JEM-ARM200F).
[0097] Measurement conditions:
[0098] For samples thinned using the FIB (Focused Ion Beam) method, observations were conducted at an accelerating voltage of 200 kV.
[0099] (Joint strength)
[0100] For joints 5 and 5A in each example, the joint strength was determined using the crack opening method. Specifically, when the joint strength exceeded 1.75 J / m... 2At that time, no peeling occurred near the bonding layer 2B, and the main body of the bonding bodies 5 and 5A was destroyed.
[0101] [Table 1]
[0102]
[0103] [Table 2]
[0104]
[0105] In Comparative Examples 1 and 2, the oxygen ratio in the amorphous layer was slightly lower than that in the supporting substrate, resulting in lower bonding strength in both cases.
[0106] In Examples 1, 2, and 3, the oxygen ratio in the amorphous layer was higher than that in the supporting substrate, resulting in significantly improved bonding strength. No peeling occurred during the polishing of the piezoelectric material substrate.
[0107] (Example 4, Comparative Example 3)
[0108] In Example 1, the material of the support substrate was changed to sapphire, and the FAB irradiation dose was also changed. Otherwise, joints 5 and 5A were fabricated in the same manner as in Example 1, and the oxygen ratio, argon ratio, and bonding strength of each part were measured. The results are shown in Table 3.
[0109] [Table 3]
[0110]
[0111] In Comparative Example 3, the oxygen ratio in the amorphous layer was slightly lower than that in the supporting substrate, resulting in lower bonding strength.
[0112] In Example 4, the oxygen ratio in the amorphous layer is higher than that in the supporting substrate, resulting in a significant improvement in bonding strength, and no peeling occurs during the polishing of the piezoelectric material substrate.
[0113] (Example 5, Comparative Example 4)
[0114] In Example 1, the material of the support substrate was changed to cordierite, and the FAB irradiation dose was also changed. Otherwise, joints 5 and 5A were fabricated in the same manner as in Example 1, and the oxygen ratio, argon ratio, and bonding strength of each part were measured. The results are shown in Table 4.
[0115] [Table 4]
[0116]
[0117] In Comparative Example 4, the oxygen ratio in the amorphous layer was the same as that in the supporting substrate, resulting in lower bonding strength.
[0118] In Example 5, the oxygen ratio in the amorphous layer is higher than that in the supporting substrate, resulting in a significant improvement in bonding strength, and no peeling occurs during the polishing of the piezoelectric material substrate.
[0119] (Example 6, Comparative Example 5)
[0120] In Example 1, the material of the support substrate was changed to andalusite, and the FAB irradiation dose was also changed. Otherwise, joints 5 and 5A were fabricated in the same manner as in Example 1, and the oxygen ratio, argon ratio, and bonding strength of each part were measured. The results are shown in Table 5.
[0121] [Table 5]
[0122]
[0123] In Comparative Example 5, the oxygen ratio in the amorphous layer was slightly lower than that in the supporting substrate, resulting in lower bonding strength.
[0124] In Example 6, the oxygen ratio in the amorphous layer is higher than that in the supporting substrate, resulting in a significant improvement in bonding strength, and no peeling occurs during the polishing of the piezoelectric material substrate.
[0125] (Example 7, Comparative Example 6)
[0126] In Example 1, the material of the support substrate was changed to transparent alumina, and the FAB irradiation dose was also changed. Otherwise, joints 5 and 5A were fabricated in the same manner as in Example 1, and the oxygen ratio, argon ratio, and bonding strength of each part were measured. The results are shown in Table 6.
[0127] [Table 6]
[0128]
[0129] In Comparative Example 6, the oxygen ratio in the amorphous layer was slightly lower than that in the supporting substrate, resulting in lower bonding strength.
[0130] In Example 7, the oxygen ratio in the amorphous layer is higher than that in the supporting substrate, resulting in a significantly improved bonding strength, and no peeling occurs during the polishing of the piezoelectric material substrate.
Claims
1. A conjugate, characterized in that: have: a support substrate comprising a metal oxide; Piezoelectric material substrate; The bonding layer is provided between the support substrate and the piezoelectric material substrate and is composed of Si (1-x) O x , where 0.008≤x≤0.408; and an amorphous layer disposed between the bonding layer and the supporting substrate, The oxygen ratio in the amorphous layer is higher than the oxygen ratio in the supporting substrate.
2. The joint body according to claim 1, characterized in that: The metal oxide is selected from the group consisting of sialon, sapphire, cordierite, mullite and alumina.
3. The joint body according to claim 1 or 2, characterized in that: The piezoelectric material substrate is selected from the group consisting of lithium niobate, lithium tantalate, and a lithium niobate-lithium tantalate solid solution.
4. The joint body according to claim 1 or 2, characterized in that: The bonded body includes an intermediate layer provided between the bonding layer and the piezoelectric material substrate.
5. An elastic wave element, characterized in that: The invention comprises: the bonded body according to any one of claims 1 to 4, and electrodes provided on the piezoelectric material substrate.
Citation Information
Patent Citations
[kiyoujiseisankatetsunoseihou[kiyoujiseisankatetsunoseihou]
JP1983014727B2
Method and manufacturing surface acoustic wave device
US20040226162A1
Bonded bodies and acoustic wave devices
US20190007022A1